STRATEGI PENGEMBANGAN USAHA KULINER KHAS KOTA MEDAN (Studi Pada Bika Ambon Zulaikha Jalan Mojopahit) - Monica Beatrice Anggreini Hutabarat (Jurnal Niaga & Bisnis (e-journal), 2015)
ABTRACT This study aims to determine how the business strategy in developing businesses in Stores Zulaikha Bika Ambon. Forms of research used in this study was a descriptive study with a qualitative approach, in which data collection techniques based on interviews, documentation, and literature. The data analysis technique used is descriptive data analysis is to describe and interpret the data that has been obtained from the field and interviews with informants who have been determined in advance. Data were obtained from interviews and documentation collected, compiled and analyzed in order to discover how business strategies in developing businesses in Stores Bika Ambon Zulaikha and input as the solution of decision making in the issues discussed. The results of this study indicate that the business strategy adopted by Bika Ambon shop Zulaikha still using traditional strategies in implementing marketing strategies and customer satisfaction strategy in particular. Strategy halal labeling on each product became the mainstay Store Bika Ambon Zulaikha in attracting buyers, in addition to flavor variations for each product more in compare competitors. Besides, Store Bika Ambon Zulaikha in implementing its business strategy, especially marketing strategy is still constrained and experiencing barriers to development through a media campaign and lack of openness in pricing on any product. Meanwhile on customer satisfaction strategy, motivation for employees required to improve the performance and quality of service is more than what has been done Store Bika Ambon Zulaikha today.   Keywords       : Business Strategy and Business Development, Culinary Typical Medan